Attitude of Asians to calcium and vitamin D rich foods and supplements: a systematic review - Chin, Yi Chan; Norazlina Mohamed,; Soelaiman, Ima-Nirwana; Chin, Kok-Yong (Penerbit Universiti Kebangsaan Malaysia, 2018)
The prevalence of osteoporosis is increasing in Asian countries. Optimum calcium intake and vitamin D level are important to prevent osteoporosis. The attitude of the society towards calcium food sources and supplements, as well as sun exposure, influence their bone health practices. This review aimed to summarize the current literature on the attitude of Asians on calcium and vitamin D rich foods and supplements to understand the barriers among the Asians in achieving adequate calcium intake and vitamin D level. Studies showed that most Asians have a negative attitude towards calcium-rich foods, mainly dairy products due to lactose intolerance, aversion to the taste of dairy products or the absence of motivation. Although they took supplements to fill the gap in their diet, they were not aware of the daily recommended intake of calcium. Besides, the majority of them have a negative attitude towards sun exposure due to the fear of getting skin cancer or tanning. As a conclusion, most of Asians are still not aware of the importance of calcium and vitamin D for their health and their negative attitude must be corrected to prevent the rise of osteoporosis.